Correlation Between the Bacterial and Fungal Profiles from the Clinical Specimens with the CD4 Counts and the NLR Values of HIV/AIDS Patients at Tertiary Referral Hospital in Indonesia - Nafdzu Makhmudatul Muna, - (Sami Publishing Company, 2023)
Human immunodeficiency virus (HIV) poses a significant problem for the global public health with high morbidity and mortality rates. HIV/AIDS cases in Indonesia, the country with the fifth highest risk of HIV/AIDS in Asia, continue to increase. A decrease in CD4 levels indicates an increase in the opportunistic infection rates of HIV patients. In addition, Neutrophil to Lymphocyte Ratio (NLR) can serve as the basis for bacterial infection, infection rate, and antibiotic therapy. This observational analytic study applies a retrospective cross-sectional design and aims to observe the correlation between bacterial and fungal profiles of clinical specimens and the CD4 cell counts and the NLR values of HIV/AIDS inpatients at Dr. Soetomo Tertiary Referral Hospital from September 2021 to August 2022. A total of 192 bacterial and fungal identification test results from 76 patients were collected, consisting of 83.3% bacterial culture tests, consisting of 52.5% negative cultures, 12% gene expert TB tests, and 4.7% fungal culture tests. Pseudomonas aeruginosa and Escherichia coli ESBL were the highest numbers of Gram-negative bacteria found in this study, amounting to 51.33%, followed by Streptococcus viridans, the highest number of Gram-positive bacteria found in this study, amounting to 48.67%. A total of 34.2% commensal bacteria and 21.05% Multi-Drug Resistant Organism (MDRO) bacteria were also found in this study. The gene expert TB tests resulted in 73.9% undetected M. tuberculosis, while the fungal culture tests resulted in 88.9% Candida albicans. Furthermore, there was no correlation between the bacterial and fungal profiles from clinical specimens with CD4 counts or NLR values in HIV/AIDSinfected patients.